Application of Website-Based Fieldwork Practice Information System - Linda Fatmawati; Adhie Thyo Priandika; Ade Dwi Putra (Journal of Information Technology, Software Engineering and Computer Science, 2023)
Field work practice is a program that must be followed by Yadika Pagelaran Vocational School students which is useful for training students to be able to adapt and provide experience in the world of work. However, in its management, SMK Yadika Pagelaran still uses manual methods in several processes such as recording student daily activity journals, collecting street vendors reports and processing student transcripts. In this study, a website-based field work practice system will be built using the waterfall design method which is useful for facilitating data management in the implementation of street vendors at SMK Yadika Pagelaran. This research was designed using UML system design and system testing using black box testing. The results achieved from this research are a website-based field work practice system for managing the implementation of street vendors used by street vendors admins, students, school supervisors and company supervisors. Tests in this research system produce a percentage of 100% so that the system is said to be very feasible to use. With this system, it is hoped that it can help all relevant parties in the process of implementing field work practices at SMK Yadika Pagelaran